Virological characteristics correlating with SARS-CoV-2 spike protein fusogenicity - Begum, MST Monira; Ichihara, Kimiko; Takahashi, Otowa; Nasser, Hesham; Jonathan, Michael; Tokunaga, Kenzo; Yoshida, Isao; Nagashima, Mami; Sadamasu, Kenji; Yoshimura, Kazuhisa; , The Genotype to Phenotype Japan (G2P-Japan) Consortium; Sato, Kei; et al. (Frontiers in Virology, 2024)
The severe acute respiratory syndrome coronavirus (SARS-CoV-2) spike (S) protein is essential in mediating membrane fusion of the virus with the target cells. Several reports demonstrated that SARS-CoV-2 S protein fusogenicity is reportedly closely associated with the intrinsic pathogenicity of the virus determined using hamster models. However, the association between S protein fusogenicity and other virological parameters remains elusive.In this study, we investigated the virological parameters (e.g., S1/S2 cleavage efficiency, plaque size, pseudoviral infectivity, pseudovirus entry efficiency, and viral replication kinetics) of eleven previous variants of concern (VOCs) and variants of interest (VOIs) correlating with S protein fusogenicity. S protein fusogenicity was found to be strongly correlated with S1/S2 cleavage efficiency and plaque size formed by clinical isolates. However, S protein fusogenicity was less associated with pseudoviral infectivity, pseudovirus entry efficiency, and viral replication kinetics. Taken together, our results suggest that S1/S2 cleavage efficiency and plaque size could be potential indicators to predict the intrinsic pathogenicity and S protein fusogenicity of newly emerged SARS-CoV-2 variants.